We, the people : politics of national peculiarity in Southeastern Europe - Mishkova, Diana, 1958- (Central European University Press, 2009)
Analyzes the processes of nation-building in nineteenth and early-twentieth-century south-eastern Europe. A product of transnational comparative teamwork, this collection represents a coordinated interpretation based on ten varied academic cultures and traditions.